Ca(2+)-independent F-actin assembly and disassembly during Fc receptor- mediated phagocytosis in mouse macrophages (The Rockefeller University Press, 1991)
Phagocytosis of IgG-coated particles by macrophages is presumed to involve the actin-based cytoskeleton since F-actin accumulates beneath forming phagosomes, and particle engulfment is blocked by cytochalasins, drugs that inhibit actin filament assembly. However, it is unknown whether Fc receptor ligation affects the rate or extent of F- actin assembly during phagocytosis of IgG-coated particles. To examine this question we have used a quantitative spectrofluorometric method to examine F-actin dynamics during a synchronous wave of phagocytosis of IgG-coated red blood cells by inflammatory mouse macrophages. We observed a biphasic rise in macrophage F-actin content during particle engulfment, with maxima at 1 and 5 min after the initiation of phagocytosis. F-actin declined to resting levels by 30 min, by which time particle engulfment was completed. These quantitative increases in macrophage F-actin were reflected in localized changes in F-actin distribution. Previous work showed that the number of IgG-coated particles engulfed by macrophages is unaffected by buffering extracellular calcium or by clamping cytosolic free calcium concentration ([Ca2+]i) to very low levels (Di Virgilio, F., B. C. Meyer, S. Greenberg, and S. C. Silverstein. 1988. J. Cell Biol. 106: 657-666). To determine whether clamping [Ca2+]i in macrophages affects the rate of particle engulfment, or the assembly or disassembly of F- actin during phagocytosis, we examined these parameters in macrophages whose [Ca2+]i had been clamped to approximately less than 3 nM with fura 2/AM and acetoxymethyl ester of EGTA. We found that the initial rate of phagocytosis, and the quantities of F-actin assembled and disassembled were similar in Ca(2+)-replete and Ca(2+)-depleted macrophages. We conclude that Fc receptor-mediated phagocytosis in mouse macrophages is accompanied by an ordered sequence of assembly and disassembly of F-actin that is insensitive to [Ca2+]i.